Growth and yield performances of tiller mutilated hybrid rice variety Dhani Gold - Rahman, Mst Farzana; Anwar, Md. Parvez; Hossain, Md Delwar; Rashid, Md Harun Or; Munira, F N Kamarum; Jahan, Israt (Fundamental and Applied Agriculture, 2020)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July-October 2016 to investigate into the tolerance of hybrid rice variety Dhani Gold to tiller separation. The experimental treatments included (a) 3 times of tiller separation viz. tiller separation at 3 weeks after transplanting (3 WAT), 4 WAT and 5 WAT, and (b) 5 levels of number of tillers separated hill−1 viz. intact hill, 1 tiller, 2 tillers, 3 tillers and 4 tillers separated hill−1. The experiment was laid out in randomized complete block design with three replications. Tiller separation adversely affected the growth, in terms of plant stature and tillering ability, of Dhani Gold. Intact hill showed taller plants and higher number of tillers compared to tiller mutilated hills. With the delay in tiller separation, plant height of Dhani Gold was gradually decreased but tillering ability gradually increased. Effective tiller production was reduced only when tillers were separated after 4 WAT, but delay in tiller separation en- hanced grains panicle−1 production. Early separation of tillers up to 4 WAT did not affect grain yield, but separation after 4 WAT reduced grain yield of Dhani Gold. Separation of only 1 tiller hill−1 at 3 or 4 WAT and intact hills produced statistically similar yield. To conclude, hybrid rice variety Dhani Gold can tolerate tiller separation to some extent. Only one tiller can be separated before 4 WAT without causing any yield reduction of mother plant, but tiller separation after 4 weeks will reduce the yield of mother plant. Therefore, farmers may be advised to separate tillers from Dhani Gold within 4 WAT for re-transplanting as a post flood crop after recession of flood water.